The Role of Aswaja Values in Enhancing the Professional Ethics of Notaries in Indonesia - Agustan, Fajar (AL- IKTISAB Journal of Islamic Economic Law, 2025)
This research discusses the influence of Aswaja values on the professional ethics of notaries in Indonesia. The professional ethics of notaries, derived from the Greek word "ethos," encompass moral guidelines and social norms applied in the practice of notarial duties. Notaries in Indonesia are expected to perform their duties with integrity, adherence to the law, and in compliance with the code of ethics established by the Indonesian Notaries Association (INI). This code of ethics serves to regulate the behavior of notaries and ensure professionalism and integrity in providing legal services to the community. The methodology used in this rsearch is qualitative with normative legal approach. The results is, the values of Aswaja, upheld by Nahdlatul Ulama (NU), such as tasamuh (tolerance), amar ma’ruf nahi munkar (enjoining what is right and forbidding what is wrong), tawasuth and i'tidal (moderation and justice), and tawazun (balance), are highly relevant in shaping the professional ethics of notaries. These values encourage notaries to act honestly, fairly, and responsibly in carrying out their duties. For example, the value of tasamuh teaches tolerance and mutual respect, which are crucial in the professional and social interactions of notaries. Amar ma’ruf nahi munkar emphasizes the importance of acting rightly and avoiding wrongdoing, which is essential in maintaining the integrity of the profession. Tawasuth, i'tidal, and tawazun, meaning moderation and balance, urge notaries to be fair and prudent in every decision and action they take. By integrating Aswaja values into professional ethics, notaries in Indonesia can enhance the quality of their services, maintain public trust, and ensure the enforcement of fair and dignified laws. This research demonstrates that the application of Aswaja values in the professional ethics of notaries can strengthen integrity and professionalism and contribute to the creation of a better legal environment in Indonesia.